THE HOLISTIC APPROACH IN UNDERSTANDING THE COMPLEXITY OF SEXUAL HARASSMENT CASES IN INDONESIA - Fadhillah Mahendra; Violin Revalika Arwis (Problematika Hukum, 2022)
Sexual harassment cases are common cases that occur not only in Indonesia but also in the world. Cases of sexual harassment also often receive the attention of the public, state officials, and the law. Even though there is a legal framework in Indonesia, low incident reporting is still a challenge. This highlights the need for a comprehensive understanding of the cultural nuances that shape perceptions and responses to such behavior. Cases of sexual harassment do not only happen to women but also to men. Those who became victims also came from various ages, from toddlers to even the elderly. This abstract will focus on the aims of why we need to minimize cases of sexual harassment in IndonesiaLegal framework; Indonesia; Sexual Harassment; Social-Culture Society.